Dynamic behavior of heat and hydrogen transfer in a metal hydride cooling system - Kang, BH; Park, CW; Lee, CS (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
An experimental study has been carried out to investigate transient transport processes of hydrogen and heat between two coupled reactors in a metal hydride cooling system. This problem is of particular interest in the design of metal hydride thermal energy conversion systems, such as refrigerators, heat pumps, and thermal storage systems. A pair of hydride reactors are designed to extend the contact surface between hydride materials and Bowing hydrogen for fast kinetics. Dynamic correlations of pressure-temperature and temperature-concentration are investigated in a typical operational condition. The amount of hydrogen gas transferrable between the paired metal hydrides is measured and the optimum value of the charged hydrogen amount is found for the maximum hydrogen transfer. Copyright (C) 1996 International Association for Hydrogen Energy
Keywords: MASS-TRANSFER; PERFORMANCE; PUMP